Pattern and Predictors of Tobacco Use Among Undergraduates in Three Tertiary Institutions in North-Western Nigeria. Issue 1 (October 2022) - Ibrahim, Muhammed Sani; Sabitu, Kabir; Olorukooba, Abdulhakeem Abayomi; Muhammad, Nuru Suleiman; Abubakar, Aisha A.; Asuke, Sunday
Background: Tobacco use is associated with medical, social and economic problems. There is paucity of data on tobacco use among undergraduates in northern Nigeria. This study assessed pattern and predictors of tobacco use among undergraduates in Zaria, North-western Nigeria. Method: It was a cross-sectional study of undergraduates in three tertiary institutions. Multi-stage sampling technique was used to select 1, 080 undergraduates. Data was collected using a questionnaire adapted from Global Adult Tobacco Survey and Global Youth Tobacco Survey. Bi-variate analysis was used to identify independent variables showing statistically significant association with current tobacco use. These were entered into step-wise logistic regression. Results: Their median age was 24 years (range:15–47). Prevalence of current tobacco use was 27.0%. About 58.7% smoked tobacco daily and 40.0% used smokeless tobacco daily. Commonest places where tobacco was used were off campus accommodation (30.2%), social center (30.2%) and bar or club (28.1%). Predictors of tobacco use were being a male [2.64(1.82–3.84)], married [2.33(1.49–3.70)], experiencing tobacco promotional activity [1.56(1.12–2.17)], willing to use promotional objects [2.06(1.35–3.14)], using of promotional objects [2.74(1.90–3.96)], and exposure to secondhand smoke [14.10(4.16–47.81)]. Predictors of non-use of tobacco were spending two years or less awaiting university admission [0.65 (0.46–0.91)], parents currently together [0.48(0.33–0.69)], and supporting ban on tobacco [0.34 (0.23–0.48)]. Conclusion: Prevalence of tobacco use and expenditure on tobacco were high. University authorities should commence programs to identify tobacco users and encourage cessation. The findings also highlight the need to establish effective tobacco surveillance system that includes students of tertiary institutions.